World War II : an encyclopedia of quotations - Langer, Howard (Westport, Conn. : Greenwood Press, 1999)
A collection of more than 1,000 quotations from speeches, news accounts, memoirs, and interviews that took place during World War II.
Includes bibliographical references (p. [431]-438) and indexes.
Booklist.
Library Journal.
Reference and Research Book News.
Young Adult.
Young Adult
Keywords: World War, 1939-1945 -- Quotations, maxims, etc. -- Encyclopedias; World War, 1939-1945 -- Quotations -- Encyclopedias